Magnetic Resonance Imaging in Giant Perianal Epidermoid - Aruna Raman Patil; Amit Bansal; Nilotpal Chakma; Ravishankar Bhat; Swarna Shivakumar (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Perianal epidermoid cyst is a rare entity and is commonly diagnosed late owing to its slow-growing nature. Imaging plays a vital role in diagnosis and differentiation from other cysts such as dermoid, tailgut, and rectal duplication cysts. Magnetic resonance imaging (MRI) is the preferred modality as uncomplicated cases show typical signal changes. Diffusion-weighted imaging has a definite additional role. We report a case of a giant perianal epidermoid diagnosed on MRI and successfully managed surgically.